Incidence and molecular characterization of Glucose‐6‐Phosphate Dehydrogenase deficiency among neonates for newborn screening in Chaozhou, China. (1st December 2014) - Yang, H.; Wang, Q.; Zheng, L.; Zhan, X.‐F.; Lin, M.; Lin, F.; Tong, X.; Luo, Z.‐Y.; Huang, Y.; Yang, L.‐Y.
Summary Introduction Glucose‐6‐phosphate dehydrogenase (G6PD) deficiency is highly prevalent in southern China. The aim of this study is to assess the extent of this disease in Chinese neonates and determine its molecular characteristics using a novel molecular screening method. Methods A total of 2500 neonates were routinely screened for G6PD deficiency using a modified fluorescent spot test (FST). PCR‐high‐resolution melting (HRM) analysis was then used for the molecular assay. Results The overall incidence of G6PD deficiency was 2.68% in our study cohort. Frequency in male population was 3.22% (44 neonates of 1365 male neonates), and in female population was 2.03% (23 neonates of 1135 female neonates). Of the 67 newborns suspected to be G6PD deficient based on FST (44 males, 23 females), 58 of 67 (87%) were detected with gene alterations. Seven kinds of mutations [c.95A>G, c.392G>T, c.493A>G, c.871G>A, c.1360C>T, c.1376G>T, and c.1388G>A] were identified by HRM analysis. Conclusion Routine newborn screening in Chaozhou, China with a relatively high prevalence of G6PD deficiency is justified and meets the World Health Organization recommendation. The usage of molecular diagnosis can favor the detection of heterozygotes which can be a supplement to regular newborn screening and useful for premarital and prenatal diagnosis for G6PD deficiency.